The effect of direct and indirect mental training on the level of motor Satisfiction in football - Abdel Al-Raheem Salami; Mohammed Kh. Asmer; Zuhair K. Al-Khashab (مجلة الرافدين للعلوم الرياضية, 2006)
Abstract: The research aims are : 1. Detecting the effect of normal , direct , and indirect methods of mental training on the level of motor satisfiction . 2. Detecting the differncess among the three research groups in the post – tests concerning the level of motor satisfiction in football . - The researchers have used the experimental method to achieve the afore Mentioned objectives , and three learning programes have been applied on three groups , the first is a control one whereas the two are experimintal , each of them is made up of (15) novice players affiliating to the Ninava governorate team under (16) years . - Having made the post-test , the resarchers concluded the following : 1. The three learning programes have a positive effect on the level of motor satisfiction . 2. There are significant differences among the three methods in the level of motor satisfiction between pre- and post – tests in the penefit of post- tests . 3. There are significant differences among the three methods of research in the group using the direct method of mental training . Finally , the researchers have recommended that : 1. The emphasis be made on the use of both the direct and indirect methods of mental training within the learning process. 2. The reliance on the motor satisfiction criterion to the measure the level of motor satisfiction. 3. The emphasis be made on the phychological and emotional aspcts of the novice players on prepearing the learning programes .